From Policy “Frames” to “Framing”: Theorizing a More Dynamic, Political Approach - van Hulst, Merlijn; Yanow, Dvora (American review of public administration, 2016)
The concept of frames or framing, especially cast as “frame analysis,” has an established history in public policy. Taking off from the work of Donald Schön and Martin Rein, we develop the idea of policy analytic framing, the more dynamic of the two terms, in ways that strengthen what we see as its promise for a more process-oriented and politically sensitive understanding of the activities it is used to characterize. We argue that such an approach needs to engage the following aspects of the work that framing does: sense-making; selecting, naming, and categorizing; and storytelling. In addition, frame theorizing needs to engage not only the way issues are framed but also the intertwining of framing and frame-makers’ identities, and the meta-communicative framing of policy processes.